COVID‐19 and urology: a comprehensive review of the literature. (12th May 2020) - Puliatti, Stefano; Eissa, Ahmed; Eissa, Radwa; Amato, Marco; Mazzone, Elio; Dell'Oglio, Paolo; Sighinolfi, Maria Chiara; Zoeir, Ahmed; Micali, Salvatore; Bianchi, Giampaolo; Patel, Vipul; Wiklund, Peter; et al.
Abstract : Objective: To discuss the impact of COVID‐19 on global health, particularly on urological practice and to review some of the available recommendations reported in the literature. Material and Methods: In the current narrative review the PubMed database was searched to identify all the related reports discussing the impact of COVID‐19 on the urological field. Results: The COVID‐19 pandemic is the latest and biggest global health threat. Medical and surgical priorities have changed dramatically to cope with the current challenge. These changes include postponements of all elective outpatient visits and surgical procedures to save facilities and resources for urgent cases and patients with COVID‐19 patients. This review discuss some of the related changes in urology. Conclusions: Over the coming weeks, healthcare workers including urologists will be facing increasingly difficult challenges, and consequently, they should adopt triage strategy to avoid wasting of medical resources and they should endorse sufficient protection policies to guard against infection when dealing with COVID‐19 patients.